Promosi Website di RW 013 Cipinang Melayu Jakarta Timur - Syukur, Agus; Puspita, Ratna; Givan, Bryan; Ashilah, Andi Nabilah Nur; Islam, Hanifan Huzatul; Rafly, Ananda; Aji, Bintang Azhara (PT. Riset Press International, 2024)
A website is an information system service that is very important in providing and informing about a product or service to a company, agency, or state and educational institution. This activity aims to provide understanding to the residents of RW 013 Cipinang Melayu, East Jakarta regarding the use and benefits of websites in providing information and services. The output targeted in this activity is to help residents understand the benefits of websites and help them in creating websites.